142k views
2 votes
Jerry solved this equation: 3 ( x −

1
4
) =
13
6

1. 3x −
3
4
=
13
6

2. 3x −
3
4
+
3
4
=
13
6
+
3
4

3. 3x =
26
12
+
9
12

4. 3x =
35
12

5. (
3
1
)
3
1
x =
35
12
(
3
1
)

6. x =
105
12

In which step did Jerry make an error?
In step 2, he should have subtracted Three-fourths from both sides.
In step 3, he should have found an LCD of 10.
In step 4, he should have subtracted 9 from 26.
In step 5, he should have multiplied both sides by One-third.

2 Answers

3 votes

Answer:

Step five

Step-by-step explanation: The reason i picked this step becuase it doesnt go with the equation

User Gordon Truslove
by
6.0k points
7 votes

Answer:

In step 5, he should have multiplied both sides by One-third.

Explanation:

User AshtonKJ
by
6.3k points